To solve the equation \( 3(-x + 3) - 2x + 3 = -38 \), we can follow these steps:
-
Distribute the \( 3 \) in the first term: \[ 3(-x) + 3(3) - 2x + 3 = -38 \] This simplifies to: \[ -3x + 9 - 2x + 3 = -38 \]
-
Combine like terms: \[ -3x - 2x + 9 + 3 = -38 \] This further simplifies to: \[ -5x + 12 = -38 \]
-
Isolate the variable term by subtracting \( 12 \) from both sides: \[ -5x + 12 - 12 = -38 - 12 \] Which gives us: \[ -5x = -50 \]
-
Divide by \(-5\) to solve for \( x \): \[ x = \frac{-50}{-5} = 10 \]
Thus, the solution is: \[ \boxed{10} \]